2020
DOI: 10.2147/idr.s264882
|View full text |Cite
|
Sign up to set email alerts
|

<p>ACEIs and ARBs and Their Correlation with COVID-19: A Review</p>

Abstract: Although some animal studies suggested that the use of ACEIs/ARBs could contribute for the prevention and treatment of the effects of the COVID-19 infection, there are also contradictory scenarios indicating that their use may exacerbate the deleterious conditions of the infection. As a result of the paradoxical issue of using ACEIs/ARBs during COVID-19, it is still an area requiring extended investigation to prove. Additionally, a trial evidence of their efficacy and the possible benefit risk analysis of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…It is pertinent to mention here that using combination of ACEIs and ARBs in COVID-19 patients not only lower blood pressure but also may maximize organ protection and was therefore used concurrently. Also, by stabilizing www.nature.com/scientificreports/ and internalization of ACE2-AT1R interaction, ACEIs/ARBs could prevent COVID-19 viral entry 21 . This may be another reason for using this combination in the management of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is pertinent to mention here that using combination of ACEIs and ARBs in COVID-19 patients not only lower blood pressure but also may maximize organ protection and was therefore used concurrently. Also, by stabilizing www.nature.com/scientificreports/ and internalization of ACE2-AT1R interaction, ACEIs/ARBs could prevent COVID-19 viral entry 21 . This may be another reason for using this combination in the management of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patients with higher troponin levels had also increased markers of inflammation, including C-reactive protein, interleukin (IL)-6, ferritin, lactate dehydrogenase (LDH), high neutrophil count, and high amino-terminal pro-B–type natriuretic peptide ( 158 ). Despite it was initially hypothesized that COVID-19 patients with pre-existing cardiovascular morbidities and treated with ACE inhibitors (ACEi) or angiotensin receptor blockers (ARBs) ( 155 , 159 , 160 ). could be at increased risk for severe SARS-CoV-2 infection, a recent retrospective study on COVID-19 patients with hypertension showed that ACEI/ARB therapy attenuated the inflammatory response ( 161 ).…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%
“…Therefore, reduction and downregulation of ACE2 by SARS-CoV-2 lead to an elevation of vasoconstrictor Ang II causing vasoconstriction, hypertension, and induction of inflammatory and pro-inflammatory activations. A high Ang II concentration is directly linked to ALI and ARDS in Covid-19, so that both angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are able to reduce the harmful effect of Ang II on the lung through ACE2 upregulation ( 44 ).…”
Section: Estrogen and Renin–angiotensin System In Covid-19mentioning
confidence: 99%